STUDI KARAKTERISTIK KUBANGAN BADAK JAWA (Rhinoceros sondaicus Desmarest 1822) DI TAMAN NASIONAL UJUNG KULON - Yanto Santosa; Cory Wulan; Agus Hikmat (Department of Forest Resources Conservation and Ecotourism - IPB University, 2010)
The characteristic of wallow can be one of standard or criteria of the javan rhino habitat that need for creating the second habitat which will be used for selection strategy of further javan rhino’s wallow. The objective of this study is to identify the wallow characteristic of javan rhino. The results of this study is hopefully used for the consideration in determining the second habitat of java rhino and for the basics information of habitat development of javan rhino insitu conservation. The data that were collected consisted of physical characteristic javan rhino’s wallow i.e. the length and the width of wallow, the depth of mud and water of wallow, water pH inside the wallow, the height of wallow site, the temperature and humidity, and the distance from wallow to the coastal, river, and from human access. Keywords : Javan Rhinoceros, wallow, second habitat.